Assessment of the financial health of regional emergency medical services in the Czech Republic using the BAMF model - Kraftová, Ivana; Kašparová, Lenka (Journal of Business Economics and Management, 2017)
The focus of the paper is the evaluation of the financial health of selected public service providers. As part of the research we used a specially designed model of balance-sheet analysis for BAMF municipal companies. Used on a sample of 14 regional providers of emergency medical services in the Czech Republic from 2010–2014, we assessed the level and variability of the aggregate financial health indicator BAMF and its components, five sub-indicators. It turns out that the financial health of these subjects, although displaying significant similarities are not free of extreme values that in practice require more attention, or more precisely, deeper analysis. The authors conclude that the model is relatively easy to apply in practice and can contribute to the better financial health management of public sector bodies. At the same time, the BAMF model can be considered an addition to the theory of financial analysis.